Comparison of different cryoprotective agents on swamp buffalo semen cryopreservation - Herbowo, M. T.; Arifiantini, R. I.; Karja, N. W. K.; Sianturi, R. G. (Journal of the Indonesian Tropical Animal Agriculture, 2020)
Present study aimed to determine the effectivenessof dimethylformamide (DMF)as cryoprotective agent (CPA) by determining its optimum concentration inTris Eggyolk (TEY) extender on the quality of post-thaw swamp buffalo semen. Only ejaculates having > 60% sperm motility were divided into eight s tubes. Four tubes were diluted in TEY with 4, 5, 6, 7% of glycerol and four other tubes were diluted in TEY with 4, 5, 6, 7% of DMF. Diluted semen then packed into ministraw (0.25 mL), equilibrated at 4°C for 4 hours and freezed at 8 cm above liquid nitrogen vapour for 10 minutes and then stored at liquid nitrogencontainer. After 24 hours of storage, straws were thawed at 37°C for 30 seconds. The result showed that sperm motility after equilibration tend to be the same at all four glycerol concentrations, whereas the decrease in motility was highest in extenders with a DMF concentration of 7% (P <0.05). Post-thaw sperm motility and recovery rate in TEY extender containing 5% DMF or 7% glycerol were highest (P<0.05) than other glycerol or DMF concentration. Sperm viability and membrane integrity did not differ among TEY containing 6% or 7% glycerol, both  were higher (P<0.05) than 4% or 5% glycerol. Viability and membrane integrity of sperm in 5% DMF was superior (P<0.05) to 4%, 6% or 7%. This research concluded that 5% DMF or 7% glycerol was considered to be the most suitable CPAs for swamp buffalo semen cryopreservation.